Finding sacral: Developmental evolution of the axial skeleton of odontocetes (Cetacea). Issue 4 (20th July 2017) - Buchholtz, Emily A.; Gee, Jessica K.
Abstract : Axial morphology was dramatically transformed during the transition from terrestrial to aquatic environments by archaeocete cetaceans, and again during the subsequent odontocete radiation. Here, we reconstruct the sequence of developmental events that underlie these phenotypic transitions. Archaeocete innovations include the loss of primaxial/abaxial interaction at the sacral/pelvic articulation and the modular dissociation of the fluke from the remainder of the tail. Odontocetes subsequently integrated lumbar, sacral, and anterior caudal vertebrae into a single torso module, and underwent multiple series‐specific changes in vertebral count. The conservation of regional proportions despite regional fluctuations in count strongly argues that rates of somitogenesis can vary along the column and that segmentation was dissociated from regionalization during odontocete evolution. Conserved regional proportions also allow the prediction of the location and count of sacral homologs within the torso module. These predictions are tested with the analysis of comparative pudendal nerve root location and geometric morphometrics. We conclude that the proportion of the column represented by the sacral series has been conserved, and that its vertebrae have changed in count and relative centrum length in parallel with other torso vertebrae. Although the sacral series of odontocetes is de‐differentiated, it is not de‐regionalized.